2015
DOI: 10.1088/0004-637x/809/1/95
|View full text |Cite
|
Sign up to set email alerts
|

THE MORPHOLOGIES OF MASSIVE GALAXIES FROMz∼ 3—WITNESSING THE TWO CHANNELS OF BULGE GROWTH

Abstract: We quantify the morphological evolution of z ∼ 0 massive galaxies (M * /M ⊙ ∼ 10 11.2±0.3 ) from z ∼ 3 in the 5 CANDELS fields. The progenitors are selected using abundance matching techniques to account for the mass growth. The morphologies of massive galaxies strongly evolve from z ∼ 3. At z < 1, the population well matches the massive end of the Hubble sequence, with 30% of pure spheroids, 50% of galaxies with equally dominant disk and bulge components and 20% of disks. At z ∼ 2 − 3 however, there is a majo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 110 publications
13
71
0
Order By: Relevance
“…This is consistent with the idea that compact SFGs are formed from extended SFGs, which are mostly disk dominated at low z, by increasing their central densities. The evolution toward disk-like morphologies with progressively bigger cores is consistent with the prominence of disks with bulges among massive SFGs at z 1  , as reported in previous works (e.g., Bruce et al 2012Bruce et al , 2014aBuitrago et al 2013;McLure et al 2013;Mortlock et al 2013;Lang et al 2014;Huertas-Company et al 2015). Note that rejuvenation and/or the re-growth of a star-forming disk in compact SFGs is also a possibility, although the increasing number of quiescent galaxies with time suggests that the net flow of galaxies is preferentially toward compaction and quenching.…”
Section: Galaxy Morphologies In the Sfrsupporting
confidence: 90%
“…This is consistent with the idea that compact SFGs are formed from extended SFGs, which are mostly disk dominated at low z, by increasing their central densities. The evolution toward disk-like morphologies with progressively bigger cores is consistent with the prominence of disks with bulges among massive SFGs at z 1  , as reported in previous works (e.g., Bruce et al 2012Bruce et al , 2014aBuitrago et al 2013;McLure et al 2013;Mortlock et al 2013;Lang et al 2014;Huertas-Company et al 2015). Note that rejuvenation and/or the re-growth of a star-forming disk in compact SFGs is also a possibility, although the increasing number of quiescent galaxies with time suggests that the net flow of galaxies is preferentially toward compaction and quenching.…”
Section: Galaxy Morphologies In the Sfrsupporting
confidence: 90%
“…It has been suggested that dry mergers are the main driver for this late size evolution, expanding their envelope by means of small satellite accretion (Naab et al 2009;Bell et al 2004). Indeed, z ∼ 1 has been identified as an epoch of galaxy merging (Hammer et al 2005;Kaviraj et al 2015), in which the progenitors of ETG increase in size and mass in proportion to one another, following approximately ∆ log R e ∼ 2 × ∆ log M (van Dokkum et al 2010Dokkum et al , 2015Huertas-Company et al 2015). This relation predicts that from z = 2 to 0.4 ETGs with a presentday mass of 3 × 10 11 increase their effective radii from R e ∼ 2.5 to 6 kpc, and their stellar mass by a factor of ∼ 1.5.…”
Section: Discussion: Sfh Constraints On Galaxy Formation Scenariosmentioning
confidence: 99%
“…In this respect, mounting evidence for a nearly environment-independent flattening in the star formation rate-stellar mass relation at high Mstar (e.g., Erfanianfar et al 2016, and references therein), paralleling an increased incidence of bulge-dominated galaxies, is also suggestive. The increase in host velocity dispersion may in fact be correlated with the growth of a central black hole; the associated feedback can reduce star formation, though alternative explanations in terms of, e.g., morphological transformations, may still be viable solutions (e.g., Martig et al 2009;Huertas-Company et al 2015).…”
Section: Implications For the Co-evolution Of Black Holes And Galaxiesmentioning
confidence: 99%